Preferences for chlamydia testing and management in Hong Kong: a discrete choice experiment. (17th September 2021) - Ong, Jason J; Fairley, Christopher K; Hocking, Jane S; Turner, Katy M E; Booton, Ross; Tse, Desiree; Wong, William W C W
Abstract : Objectives: As most chlamydia cases are asymptomatic, regular testing and timely management may be necessary for control. We aimed to determine the preferences of people living in Hong Kong for chlamydia testing and management services. Methods: An online panel of sexually active individuals living in Hong Kong completed the survey with two discrete choice experiments (DCEs). The first DCE examined the preferred attributes of a chlamydia testing service (cost, location, appointment time, speed of results, delivery of results and availability of other STI testing). The second DCE examined the preferred attributes of a chlamydia management service (cost, access to patient-delivered partner therapy, location, travel time, type of person consulted and attitude of staff). Results: In total, 520 individuals participated: average age 36.8 years (SD 9.9), 40% males and 66% had a bachelor's degree or higher. Choosing to test was most influenced by cost, followed by speed of results, delivery of results, extra STI testing, appointment available and the least important was the location of testing. Choosing to attend for management was most influenced by staff's attitude, followed by cost, who they consult, access to patient-delivered partner therapy, travel time and the least important was treatment location. Conclusion: To design effective chlamydia testing and management services, it is vital to respond to patient needs and preferences. For people living in Hong Kong, cost and staff attitude were the most important factors for deciding whether to test or be managed for chlamydia, respectively.